Digital Divide: Investigating the integration of marketing and ICTs for South African retailers expanding throughout Africa - Hill, Bethany (School of Management Studies, 2020)
Information Communication Technologies are increasingly used in organisations’ market expansion strategies. These Information communication technologies provide organisations with opportunities such as ease of communication and movement of resources, making the entry into new markets a faster and less resource heavy process. When expanding throughout the African continent, the challenge presented in using this approach is that many African markets have underdeveloped information communication technology infrastructure. In considering this barrier, the extent to which information communication technology enables market expansion throughout the African continent is the topic which has been fully analysed and discussed. An exploratory research design and a qualitative method have been used in this study. The subjects of the data collection were three key individuals selected from a large South African retailer. These three individuals job roles spanned across the marketing and IT departments and were influential in the organisation’s expansion efforts throughout Africa. The findings of this study show that the levels of information communication technology infrastructure vary vastly from country to country on the African continent, noting South Africa, Kenya, Nigeria, Zambia and Botswana as the more advanced nations with the Democratic Republic of Congo and Uganda lagging in development. The findings also show that for retailers, the retail focused technology available in South Africa is not yet available in other African nations which causes challenges in offering the same value to consumers across the board. However, the finding show that the development of cloud-based systems has assisted in the widespread use of technologies without the need of heavy investments into physical locations.